Morphological and Functional Inner and Outer Retinal Layer Abnormalities in Eyes with Permanent Temporal Hemianopia from Chiasmal Compression - Araújo, Rafael B. de; Oyamada, Maria K.; Zacharias, Leandro C.; Cunha, Leonardo P.; Preti, Rony C.; Monteiro, Mário L. R. (Frontiers in Neurology, 2017)
Purpose: To compare OCT-measured macular retinal layers in eyes with permanent temporal hemianopia from chiasmal compression and control eyes, compare regular and slow-flash multifocal electroretinography (mfERG) in patients and controls, and assess the correlation between OCT, mfERG and central visual field (SAP) data. Methods: Forty-three eyes of 30 patients with permanent temporal hemianopia due to pituitary tumors who were previously submitted to chiasm decompression and 37 healthy eyes of 19 controls were submitted to macular SD-OCT, mfERG and 10-2 SAP testing. After segmentation, the thickness of the macular retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), inner nuclear layer (INL), outer plexiform layer (OPL), outer nuclear layer (ONL) and photoreceptor layer (PRL) was measured. Amplitudes and oscillatory potentials (OP) were measured on regular and slow-flash mfERG, respectively, and expressed as the mean values per quadrant and hemifield. Results: RNFL, GCL and IPL thickness measurements were significantly reduced in all quadrants, whereas INL, OPL and PRL thicknesses were significantly increased in the nasal quadrants in patients compared to those in controls. Significant correlations between OCT and 10-2 SAP measurements were positive for the RNFL, GCL and IPL and negative for the INL, OPL and PRL. OPs and mfERG N1 amplitudes were significantly reduced in the nasal hemiretina of patients. Significant correlations were found between OP and mfERG amplitudes for inner and outer nasal hemiretina OCT measurements, respectively. Conclusions: Patients with permanent temporal hemianopia from previously treated chiasmal compression demonstrated significant thinning of the RNFL, GCL, IPL and thickening of the INL, OPL and PRL associated with reduced OP and mfERG N1 amplitudes, suggesting that axonal injury to the inner retina leads to secondary damage to the outer retina in this condition.